Preparation and characterization of functionalized cellulose nanoparticles - Benedict, Anselm Naveen (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Lignocellulosic waste’s amount is increasing at a fast rate and no proper handling method had been performed in a large scale. Therefore, this research plans to make use of paper waste. Paper waste underwent pre-treatment and functionalization using methods such as carboxymethylation under optimum conditions to produce carboxymethylcellulose (CMC). Functionalized cellulose is dissolved in NTU with the ratio of 8:6.5:8 by weight and regenerated by precipitation with non-solvent, ethanol to form regenerated cellulose. The pre-treated, functionalized and regenerated cellulose were all characterized by SEM, FTIR and degree of substitution (DS).